Defanging the snake - Haniff, Baharudin; Kam, Raslan; Mohd Azmyl, Md Yusof * (BFM Media Sdn Bhd, 2023)
The conversation on A Bit of Culture in this episode revolves around martial arts, data privacy and leadership, with BFM producer Michael Gong kicking off the conversation by reflecting on the evolution of martial arts from being a practice that’s violent, to one that’s now perceived as a form of art. Kam then reflects on the attitude people his age have towards data privacy. Are they more particular about it, or less? In the second part of the show, Azmyl Yunor ponders how leadership has changed these days to be more about making deals, rather than actually leading.